2016
DOI: 10.1002/ajp.22549
|View full text |Cite
|
Sign up to set email alerts
|

Hand preference on unimanual and bimanual tasks in strepsirrhines: The case of the ring‐tailed lemur (Lemur catta)

Abstract: Assessing manual lateralization in non-human primates could be an optimal way to understand the adaptive value of this asymmetry in humans. Though many studies have investigated hand preferences in Old and New World monkeys and apes, fewer studies have considered manual lateralization in strepsirrhines, especially in experimental tasks. This study investigated hand preferences for a unimanual and a bimanual task of 17 captive ring-tailed lemurs (Lemur catta), housed at Parco Natura Viva (VR), Italy. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In the last decades, studies evaluating hand preference in non‐human primates have increased greatly, both in captive and wild populations, and various authors suggested that a right hand bias at the population level does occur in non‐human primates (Hopkins et al, ; Humle & Matsuzawa, ; Llorente et al, ; Lonsdorf & Hopkins, ; Molesti, Vauclair, & Meguerditchian, ; Neufuss, Humle, Cremaschi, & Kivell, ; Poindexter, Reinhardt, Nijman, & Nekaris, in press; Regaiolli, Spiezio, & Hopkins, , 2018; Spinozzi, Castorina, & Truppa, ; Tabiowo & Forrester, ), but this right hand bias is not as strong and stable across different tasks as in humans (Cashmore, Uomini, & Chapelain, ; Marchant & McGrew, ). Other studies, however, with the same and different species report that lateralization in hand preference occurs only at an individual level (Brand et al, ; Leca, Gunst, & Huffman, ; Lilak & Phillips, ; Marchant & McGrew, ; Meunier & Vauclair, ; Papademetriou, Sheu, & Michel, ; Westergaard & Suomi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, studies evaluating hand preference in non‐human primates have increased greatly, both in captive and wild populations, and various authors suggested that a right hand bias at the population level does occur in non‐human primates (Hopkins et al, ; Humle & Matsuzawa, ; Llorente et al, ; Lonsdorf & Hopkins, ; Molesti, Vauclair, & Meguerditchian, ; Neufuss, Humle, Cremaschi, & Kivell, ; Poindexter, Reinhardt, Nijman, & Nekaris, in press; Regaiolli, Spiezio, & Hopkins, , 2018; Spinozzi, Castorina, & Truppa, ; Tabiowo & Forrester, ), but this right hand bias is not as strong and stable across different tasks as in humans (Cashmore, Uomini, & Chapelain, ; Marchant & McGrew, ). Other studies, however, with the same and different species report that lateralization in hand preference occurs only at an individual level (Brand et al, ; Leca, Gunst, & Huffman, ; Lilak & Phillips, ; Marchant & McGrew, ; Meunier & Vauclair, ; Papademetriou, Sheu, & Michel, ; Westergaard & Suomi, ).…”
Section: Introductionmentioning
confidence: 99%
“…The tube task consists of a tube of PVC, with variable dimensions depending on the studied species, that requires coordinated bimanual actions, that is, the primate holds the tube with one hand and uses a finger of the opposite hand, to retrieve a food reward from inside the tube. The tube task is considered a reliable and appropriate task for investigating manual asymmetries that allows consistent comparisons to be made among non‐human primates (Hopkins et al, ; Maille, Belboc'h, Rossard, Bec, & Blois‐Heulin, ; Regaiolli et al, ). Moreover, in non‐human primates the tube task has been shown to elicit hand preference that is associated with neuroanatomical asymmetry within the primary motor cortex in chimpanzees and capuchin monkeys (Hopkins & Cantalupo, ; Phillips & Sherwood, ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, strong lateralization in handedness was found early and was considered the most obvious example of cerebral lateralization and an exclusive characteristic (Perelle & Ehrman, 2005). Over the past 20 years, however, numerous systematic investigations of handedness in non-human primates (NHP) have been published (Regaiolli et al, 2016). Interestingly, these studies have not shown a similar strong hand preference in NHP as observed in humans, with contradictory findings reported thus far (Regaiolli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The roots of motor asymmetries can be traced back to early vertebrates (Vallortigara, Rogers, & Bisazza, 1999). To uncover the root of this asymmetry, researchers investigated handedness and laterality in invertebrates and vertebrates including non-human primates (MacNeilage, Neufuss et al, 2015;Regaiolli, Spiezio, & Hopkins, 2016a;Regaiolli, Spiezio, & Vallortigara 2016b;Wiper, 2017). Hopkins (2013) suggested that the lack of universal handedness in primates compared to humans was related to a qualitative difference in the way behavioural and brain asymmetries are expressed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on strepsirrhines have covered lemur species (e.g. Nelson, O'Karma, Ruperti, & Novak, 2009;Regaiolli et al, 2016a;Schnoell et al, 2014), galagos (e.g. Dodson, Stafford, Forsythe, Seltzer, & Ward, 1992;Sanford, Guin, & Ward, 1984) and pottos (Karberger, 1980), using both spontaneous and experimental conditions in both unimanual and bimanual tasks though primarily were tested in captive settings (e.g.…”
Section: Introductionmentioning
confidence: 99%